IPFS Keyword Retrieval System Based on Merkle DAG Inverted Index - Shi, Lin; Lu, Jun; Zhang, Xu; Cao, Yuan; Kang, Jinchuan (International Journal of Computer Science and Information Technology, 2024)
In recent years, IPFS, as an emerging P2P network technology, has been gaining increasing popularity. There have been numerous studies on the issue of cluster retrieval in P2P networks. This paper proposes an inverted index structure implemented through Merkle DAG, and ensures the eventual consistency of inverted index information among multiple nodes in the cluster through CRDT technology, thereby realizing a relatively effective cluster keyword retrieval scheme based on IPFS. The redundant data is reduced by improving the storage mechanism of cache. The experiments on real data sets prove the effectiveness of the proposed method.